1998
DOI: 10.1176/ps.49.11.1475
|View full text |Cite
|
Sign up to set email alerts
|

Physician-Assisted Suicide in Psychiatry: Developments in the Netherlands

Abstract: Physician-assisted suicide can now be officially and legally carried out for psychiatric patients in The Netherlands who request it, provided that criteria are met. The authors describe two recent cases of psychiatric patients whose suicides were assisted by their psychiatrist. They critically examine the guidelines for physician-assisted suicide in psychiatry. The criteria address the decision of the patient to be assisted with suicide, which must be voluntary and well considered, and the patient's desire to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 31 publications
1
41
0
3
Order By: Relevance
“…In the event that the physician feels the need to relieve the patient from unbearable suffering that shows no hope of improving in the future, the physician is required to follow various guidelines set out by the Dutch Medical Association. 11 This would relate directly to the decision and to the prognosis under the circumstances. With regard to decision related issues, the choice has to be voluntary, to be arrived at independently after rationally considering the issues and to be without any undue influence by any other parties.…”
Section: Discussionmentioning
confidence: 99%
“…In the event that the physician feels the need to relieve the patient from unbearable suffering that shows no hope of improving in the future, the physician is required to follow various guidelines set out by the Dutch Medical Association. 11 This would relate directly to the decision and to the prognosis under the circumstances. With regard to decision related issues, the choice has to be voluntary, to be arrived at independently after rationally considering the issues and to be without any undue influence by any other parties.…”
Section: Discussionmentioning
confidence: 99%
“…Such an orienting ‘landmark’ or boundary is critical in the care of a dying patient [52]. The boundaries of the therapeutic relationship might easily be transgressed if one does not recognise the similarity between the acting out of erotic feeling and the suicidal urge [53]. The psychiatrist’s therapeutic role is to be a container of anguished, despairing and hopeless emotions of a demoralised or depressed patient.…”
Section: The Psychiatrist’s Role In Assessing the Medically Ill With mentioning
confidence: 99%
“…Patients requesting EAS for a mental disorder in the Netherlands tend to be younger and female, with psychiatric diagnoses in completed EAS cases consisting of mood disorders, personality disorders, and 'unspecified' [ 18 ]. Highly publicized Dutch cases include EAS by psychiatrists of a woman for major depression and bereavement [ 7 ] and a woman for depression and anorexia nervosa [ 99 ]. Patients in the Netherlands and in Belgium who want EAS for reason of their mental illness generally ask their psychiatrists to assess their request for assisted suicide or euthanasia.…”
Section: Discussionmentioning
confidence: 99%
“…If the psychiatrist agrees, he usually takes on the additional role of prescribing the lethal overdose or carrying out euthanasia [ 3 ]. It has been observed that evaluating a patient's wish to die while treating the patient for a mental illness destroys the therapeutic boundaries that facilitate treatment [ 29 , 99 ], and the situation of a psychiatrist carrying out euthanasia on his patient is suggested to be "a highly complex situation, which has to be treated cautiously" (pp 406) [ 3 ].…”
Section: Discussionmentioning
confidence: 99%